The Relationship Between Nutritional Knowledge, Physical Activity, and Exercise Intensity with Body Composition in Yasfi Bekasi High School - Sayyida A’ini; Aridhotul Haqiyah (Universitas Negeri Semarang, 2025)
The increase in cases of overweight and obesity among adolescents is a serious challenge for public health in Indonesia. Low physical activity, high-calorie diets, and lack of nutritional knowledge are the main factors that affect the body composition and nutritional status of adolescents. This study aims to analyze the relationship between nutritional knowledge, physical activity, and exercise intensity on the body composition of students at Yasfi Bekasi High School. The research method used a quantitative approach with a cross-sectional study design on 114 respondents selected through total sampling. Data were collected through a nutritional knowledge questionnaire, the Global Physical Activity Questionnaire (GPAQ), and an exercise intensity instrument, while body composition was measured using the Bioelectrical Impedance Analysis (BIA) method. Data analysis was performed descriptively and bivariately using the Spearman Rank correlation test with a significance level of 0.05. The results showed that the majority of respondents had good nutritional knowledge (85.1%) and high physical activity (64.9%). A significant relationship was found between nutritional knowledge, physical activity, and exercise intensity with nutritional status (p < 0.05). Students with good nutritional knowledge and high physical activity tended to have a normal Body Mass Index (BMI), while respondents with low activity showed a tendency toward overweight. In conclusion, good nutritional knowledge, regular physical activity, and sufficient exercise intensity are an important combination in maintaining ideal body composition in adolescents. These findings emphasize the need for integrated nutrition education and physical activity promotion programs in schools to foster healthy lifestyles from an early age.